Role of reorganization of mitochondria structure in age-dependent changes of adrenal cortex function - Timokhina, Ekaterina P.; Yaglov, Valentin V.; Obernikhin, Sergey S.; Yaglova, Natalia V.; Nazimova, Svetlana V.; Tsomartova, Dibakhan A. (Experimental Biology and Biotechnology, 2020)
Steroidogenic activity of adrenal cortical cells is known to change significantly during postnatal development. Age-dependent changes of mitochondrial apparatus and its impact in secretory activity of the adrenal cortex are less studied. The aim was to uncover age-dependent mitochondrial dynamics in rat glomerulosa, fasciculata and reticularis cells, and to assess them together with changes in adrenal cortex morphology and function. Pubertal and postpubertal male Wistar rats were used in the research. Quantitative parameters of adrenal cortex morphology and fine structure of adrenocortical cells were examined by light and transmission electron microscopy. Production of adrenal hormones was evaluated by enzyme-linked immunosorbent assay. Discrete age-dependent changes of mitochondrial dynamics was revealed. These changes were found more sufficient for hormone production then alterations in morphology of adrenocortical zones. Association of changes in mitochondrial structure with intensity of hormone secretion demonstrate that morphological studies of adrenal cortex requires examination of fine structure for correct assessment of adrenal development.
Keywords: mitochondrion; adrenal gland; adrenal cortical cell; steroidogenesis; steroid hormones; postnatal development